Article Review: The Effect of Disintegrant Type on Tablet Disintegration Time and Dissolution Rate - Nur Shifa Rahmadina; Fathiya Nauratun Nafiah; Isna Nur Rahmawati; Anisa Jauzaa' Hasanah; Muhammad Adi Utama (Universitas Ibn Khaldun Bogor, 2026)
Tablets are the most dominant dosage form used in therapeutic practice. Disintegrant excipients are known to directly exert a significant influence on the primary quality evaluation of tablets, namely disintegration time and dissolution rate. Differences in the characteristics of various types of disintegrants lead to variations in disintegration time and dissolution performance. This study aims to examine the effect of disintegrant type on tablet disintegration time and dissolution rate. The study was conducted using a systematic literature review (SLR) method to identify, analyze, understand, and interpret relevant previous studies. The results indicate that the type of disintegrant is a key parameter determining disintegration time and dissolution rate through water penetration, particle expansion, and matrix fragmentation. Crospovidone is effective for rapid disintegration; croscarmellose sodium is suitable for hard tablets and hydrophobic active ingredients; whereas sodium starch glycolate carries a risk of gelling at high concentrations, thereby inhibiting dissolution. The effectiveness of disintegrants is influenced by concentration, manufacturing methods, and formulation accuracy. Natural disintegrants (mucilage, MCC, DBP, chitosan, modified starch, and seed powder) have the potential to serve as alternatives to synthetic disintegrants.